Parameter optimisation in duty–cycled wireless sensor networks under expected network lifetime. (20th March 2014) - Han, Guangjie; Guo, Hui; Zhang, Chenyu; Shu, Lei
In wireless sensor networks (WSNs), extensive research has focused on extending network lifetime and reducing energy consumption. The dispensable energy consumption among sensor nodes may cause network partition. Therefore, it is urgent to optimise network parameters and collect information from WSNs in an energy efficient manner during an expected network lifetime. In this paper, we propose a connected k–neighbourhood (CKN) algorithm based approach to optimise network parameters. The CKN mechanism is an energy saving algorithm with coordinated duty–cycled sleep schedule, which can adjust sensor nodes's the sleep/awake state to maximum data collection under expected network lifetime. We compare the energy consumption of network adopting CKN mechanism with that of network adopting random sleep (RS) mechanism, then further prove that we can get the maximum data collection by adjusting corresponding network parameters of the WSN. Simulation and performance analysis contribute to select the most appropriate network parameters under expected network lifetime.